Development of Electrochemical Nanosensor for the Detection of Malaria Parasite in Clinical Samples - Obisesan, Olaoluwa R.; Adekunle, Abolanle S.; Oyekunle, John A. O.; Sabu, Thomas; Nkambule, Thabo T. I.; Mamba, Bhekie B. (Frontiers in Chemistry, 2019)
In this study, Electrochemical nanosensors were developed from the synthesised metal oxide (MO) nanoparticles by supporting it on a gold electrode (Au). The activity of the developed nanosensor towards the detection of malaria biomarker (β-hematin) was determined and the optimum conditions at which the maximum detection and quantification occurred was established. β-Hematin current response at the sensors was higher compared with the bare Au electrode and followed the order Au-CuO (C) > Au-CuO (M) > Au-Fe₂O₃ (M) > Au-Fe₂O₃ (C) > Au-Al₂O₃ (M) > Au-Al₂O₃ (C) > bare Au. The developed sensors were stable with a relatively low current drop (10.61 - 17.35 %) in the analyte. Au-CuO sensor has the best performance towards the biomarker and quantitatively detected P. berghei in infected mice’s serum samples at 3.60 – 4.8 mM and P. falciparum in human blood serum samples at 0.65 – 1.35 mM concentration.